Penggunaan Pembelajaran Cooperative Learning Permainan Bola Voli Dalam Meningkatkan Hasil Passing - Yahya, Rika; Kurniawan, Febi; Efendi, Rustam (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This study aims to increase the used of volleyball cooperative learning to improve results in class VIII students of SMP Negeri 2 Cikarang Timur, Bekasi Regency in 2019/2020. The method of this research is a survey with a questionnaire as many as 20 students. The instrument used for data collection in this study was a questionnaire content assessment sheet. Based on the results of the study it was known that the level of used of volleyball learning cooperative learning in improving passing in VIII grade students at SMP Negeri 2 Cikarang Timur was included in the